Legal Protection For Child Victims Of Sexual Abuse In Palu City: A Maqashid Sharia Perspective - Adinda Octaviana; Hamiyuddin; Wahyuni (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
This study examines the implementation of legal protection for child victims of sexual abuse in Palu City from a Maqashid Sharia perspective. The research utilizes an empirical juridical design with a qualitative case approach, collecting data through interviews, observations, and documentation from the Palu City Resort Police, the Women's Empowerment and Child Protection Office (DP3A), and the Palu District Court. The findings reveal that legal protection is implemented through the PPA Unit at the police level, comprehensive assistance by DP3A including legal and psychological aid, and child-friendly judicial proceedings at the District Court. However, significant obstacles remain, including limited professional human resources, budget constraints, and persistent social stigma against victims. From the Maqashid Sharia perspective, the protection efforts in Palu City reflect the core values of hifz al-nafs (protection of life), hifz al-‘ird (protection of honor), and hifz al-nasl (protection of lineage). These measures serve as an implementation of maslahah (public interest) aimed at preventing further harm to children. Nevertheless, the realization of full benefit is still hindered by gaps in victim recovery and restitution mechanisms. The study concludes that greater institutional synergy and community education are essential to eliminate stigma and fulfill children's rights effectively according to sharia principles.